2018
DOI: 10.3846/20294913.2017.1309598
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Knowledge Retention Process: Case of Lithuanian Armed Forces

Abstract: Abstract. Knowledge management is one of the most potent means for the improvement of Lithuanian armed forces efficiency in context of transformations. Knowledge retention is one of the knowledge management processes that is related to knowledge selection, accumulation of the organization experience, renewal of the organizational memory in order to preserve the valuable knowledge from the potential loss. In order for the Lithuanian armed forces to manage the knowledge effectively and develop -it is important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This method was chosen to evaluate the complexity of the factors that influence customers' sustainable fashion perception. Using the multiple criteria method allows quantitatively to evaluate complicated phenomenon expressed by most variables (Raudeliūnienė, Meidutė, and Martinaitis, 2012;Xu, 2012;Raudeliūnienė, Davidavičienė, and Petrusevičius, 2018;Raudeliūnienė, Davidavičienė, Tvaronavičienė, and Jonuška, 2018). The multiple criteria method includes set of instruments and tools in order to evaluate research object and form decisions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was chosen to evaluate the complexity of the factors that influence customers' sustainable fashion perception. Using the multiple criteria method allows quantitatively to evaluate complicated phenomenon expressed by most variables (Raudeliūnienė, Meidutė, and Martinaitis, 2012;Xu, 2012;Raudeliūnienė, Davidavičienė, and Petrusevičius, 2018;Raudeliūnienė, Davidavičienė, Tvaronavičienė, and Jonuška, 2018). The multiple criteria method includes set of instruments and tools in order to evaluate research object and form decisions.…”
Section: Methodsmentioning
confidence: 99%
“…The test consists of such steps: calculation of the sum of ranks e_i, the sum of each participant's given ranks, the sum of all values, the average value of criteria, the sum of squared deviation, the maximum value of sum of squared deviation, a coefficient of Concordance, the significance of coefficient of Concordance (the value is compared with the one in the Chisquare including 0.05 degrees of freedom in this case), the average value of each criterion, and the values normalization (using Euclidean normalization) ( Table 2). Raudeliūnienė, Meidutė, and Martinaitis, 2012;Xu, 2012;Raudeliūnienė, Davidavičienė, and Petrusevičius, 2018;Raudeliūnienė, Davidavičienė, Tvaronavičienė, and Jonuška, 2018) The evaluative aspect Formula…”
Section: Methodsmentioning
confidence: 99%
“…Studies are beginning to emerge exploring the dimensions of knowledge retention in relation to factors affecting it. For example, Raudeliūnienė, Davidavičienė, and Petrusevičius (2018) revealed five main factors affecting knowledge retention in the military to include organisational, knowledge content, human, technological and financial. Farooq (2021) showed that knowledge retention is less in organisations with a complex organisational structure.…”
Section: Knowledge Retention In Organisationsmentioning
confidence: 99%
“…This study adopts a process-oriented approach [9,10] to sustain knowledge management practices in HEIs. This perspective suggests that an organization can build a uniqueness of knowledge potential [11][12][13] through the strategic application of knowledge strategy based on integrating the knowledge management cycle, leading to sustained organizational performance and leadership. From this perspective, it is argued in this study that investigating the influence of each knowledge management process on the subsequent processes helps ensure the sustainability of the flow of knowledge in an organization and its application, as it will assist in comprehending the contribution of each process to the knowledge management cycle in HEIs.…”
Section: Introductionmentioning
confidence: 99%